The great book of Amber : the complete Amber chronicles, 1-10 - Zelazny, Roger (Avon Books/Eos, 1999)
Showcases the epic struggle for dimension-wide supremacy. "All ten of Roger Zelzany's classic Amber fantasy novels in one book! Join Corwin, Merlin and the others in wild adventures in the lands of Amber, Earth, and the Courts of Chaos, where the powers of Amber and Chaos constantly battle for supremacy through intrigue and adventure. Revisit Amber, the land of mystery, adventure and romance. Amber, the one true world. All other worlds, including our Earth, are merely Shadows."--Publisher description.